2011
DOI: 10.1149/1.3577596
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Patterned Metal/Dielectric Surface Bonding: Mechanism, Alignment and Characterization

Abstract: An overview of the different metal bonding techniques used for 3D integration is presented. Key parameters such as surface preparation, temperature and duration of annealing, achievable wafer-to-wafer alignment and electrical results are reviewed. A special focus is done on direct bonding of patterned metal/dielectric surfaces. A mechanism for copper direct bonding is proposed based on bonding toughness measurements, SAM, XRR, XRD, and TEM analysis. Dedicated characterization techniques for such bonding are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 26 publications
5
38
0
Order By: Relevance
“…Figure 5 shows bonding toughness evolution with storage time at room temperature for copper layer deposited by ECD and PVD technique. Assembly performed with ECD copper layers exhibit an increase of bonding toughness until 2.5 J/m 2 after 120 days of storage in good agreement with literature results (Di Cioccio et al 2011). Samples which are performed with PVD copper layers exhibit low bonding toughness evolution from 0.5 to 0.7 J/m 2 after 120 days of storage.…”
Section: Copper Deposition Influencesupporting
confidence: 90%
See 3 more Smart Citations
“…Figure 5 shows bonding toughness evolution with storage time at room temperature for copper layer deposited by ECD and PVD technique. Assembly performed with ECD copper layers exhibit an increase of bonding toughness until 2.5 J/m 2 after 120 days of storage in good agreement with literature results (Di Cioccio et al 2011). Samples which are performed with PVD copper layers exhibit low bonding toughness evolution from 0.5 to 0.7 J/m 2 after 120 days of storage.…”
Section: Copper Deposition Influencesupporting
confidence: 90%
“…It has been already reported that copper-copper bonding strength performed at room temperature (20 °C) in cleanroom atmosphere increases with regards to storage time (Di Cioccio et al 2011). In this paper, we show that this bonding strengthening is not always observed.…”
Section: Introductionmentioning
confidence: 47%
See 2 more Smart Citations
“…Due to the high-hydrophilic behavior of copper surfaces after CMP treatment, some water monolayers are trapped at the bonding interface, react with metal at room temperature and create a 4 nm-thick copper oxide layer which definitively seals bonding inter- face without any volume trapped at the bonding interface. 22,23 In our study, although voids are observed in all studied cases, we assume that process parameters and surface properties result in complete bonding interface sealing: voiding appearance in bonded copper layers cannot be due to free volume trapped during bonding processes.…”
Section: Discussionmentioning
confidence: 81%